Operando Reactor-Cell with Simultaneous Transmission FTIR and Raman Characterization (IRRaman) for the Study of Gas-Phase Reactions with Solid Catalysts. - Ternero-Hidalgo, Juan José; Guerrero-Pérez, María Olga; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás; Bañares, Miguel Ángel; Portela, Raquel; Bazin, Philippe; Cleo, Guillaume; Daturi, Marco (American Chemical Society, 2020)
Raman and transmission FTIR spectroscopic techniques have been coupled in a new homemade reactor-cell designed in a joint CSIC–LCS collaboration. The setup is easily adapted to any FTIR and fiber-coupled Raman spectrometers and gas analysis techniques. It allows for simultaneous operando FTIR and Raman spectroscopic measurement, which provide complementary characterization of adsorbed species, reaction intermediates, and structural properties of the catalyst. This system was validated with the study of vanadium-based catalysts during propane oxydehydrogenation (ODH). The combined use of both spectroscopies with gas analysis techniques to measure the activity contributes to the understanding of propane ODH and the identification of the role of different oxygen species bound to vanadium sites. For example, the simultaneous characterization of the catalyst under the same conditions by IR and Raman confirms that the V═O mode has the same frequency in both spectroscopies and that bridging oxygen sites (V—O—V, V—O—Zr) present higher activity than terminal V═O bonds. These results demonstrate the high potential of the new simultaneous transmission IR–Raman operando rig to correlate the activity and the structure of catalysts, thus assisting the rational design of catalytic processes.
Keywords: Espectroscopía Raman; Catalizadores; IRRaman; Operando spectroscopy; Catalysts